Artificial oocyte activation improves cycles with prospects of ICSI fertilization failure: a sibling oocyte control study. Issue 2 (August 2019) - Li, Junsheng; Zheng, Xiaoying; Lian, Ying; Li, Ming; Lin, Shengli; Zhuang, Xinjie; Chen, Lixue; Liu, Ping; Qiao, Jie
Abstract: Research question: Does artificial oocyte activation improve clinical outcomes for patients at risk of intracytoplasmic sperm injection (ICSI) fertilization failure? Design: In this study, sibling oocytes from patients with previous ICSI failure or severe teratozoospermia were divided equally into two groups, half for artificial oocyte activation (AOA) with ionomycin after conventional ICSI and the other half for conventional ICSI only (non-AOA). The fertilization rates, cleavage rates, transferable embryo rates and blastulation rates of the two groups were compared first; the clinical pregnancy and live birth rates were also compared to assess the efficiency and safety of AOA. Result: The outcomes of the AOA group were significantly better than those of the conventional ICSI group in terms of the fertilization (50.38% versus 33.86%, respectively, P  < 0.001), cleavage (59.16% versus 39.04%, respectively, P  < 0.001) and transferable embryo rates (43.51% versus 26.69%, respectively, P  < 0.001). The blastulation (43.53% versus 36.11%, respectively), implantation (26.83% versus 15.79%, respectively), clinical pregnancy (38.46% versus 25%, respectively) and live birth rates (38.46% versus 16.67%, respectively) were not significantly different. Conclusion: This study showed that AOA improved some aspects of cycles at risk of ICSI failure by increasing the fertilization and transferable embryo rates. But blastulation, pregnancy and implantation rates were not improved. The study is limited by its small size and absence of data on cumulative outcomes.